Development of a systematic, self-consistent algorithm for the K-DEMO steady-state operation scenario - Kang, J.S.; Park, J.M.; Jung, L.; Kim, S.K.; Wang, J.; Lee, C.Y.; Na, D. H.; Im, K.; Na, Y.-S.; Hwang, Y.S. (Nuclear fusion, 2017)
An optimum plasma pressure/current density profile and corresponding heating/current drive (H/CD) determination scheme is newly developed by integrating equilibrium, stability, confinement, and H/CD, self-consistently subject to maximize the fusion gain for Korean fusion demonstration reactor (K-DEMO) steady-state operation scenarios. The integrated plasma modeling package, FASTRAN/IPS, is adopted for the integrated numerical apparatus. The target pressure profile with a pedestal structure is investigated by varying its peaking, pedestal height and width as a first step. Formation of stable equilibria is evaluated by solving the Grad-Shafranov equation and checking linear MHD stability. For the case of potentially stable equilibrium, required external heating distribution is calculated by considering both power balance and external current drive alignment to reproduce the pressure profile of the stable equilibrium. Electron/ion temperature and poloidal flux evolutions are solved with the derived heating configuration to find a steady-state scenario and achieve self-consistent plasma profiles. A self-consistent target steady-state pressure and current profile parameters are proposed through designed systematic algorithm with fusion power PF  =  2070 MW, fusion gain Q  =  19.7, and normalized beta βN  =  2.8 at toroidal field BT  =  7.4 T and plasma current IP  =  15.5 MA. Feasibility of fusion power PF  =  3000 MW operation is also explored with enhanced density and temperature limit assumption.